Review on some plants’ therapeutic effects against gastrointestinal microbes - Abdallah, Majdoline Sarah; Go, Roderick; Mustafa, Muskhazli; Nallappan, Meenakshii (Sciencedomain International, 2019)
Plants play vital roles in many health care systems, be it rural or an urban community. Plants became familiar as medicine due to the primordial ideologies and believed. Several plant parts served as medicines to so many ailments including gastrointestinal ailments, due to the fact that their active ingredients are powerful against the microbes as well as healing so many physiological abnormalities. The principal antimicrobial components were used to inhibit the growth of microbes (S. aureus, E. coli, Salmonella spp, B. cereus, and B. subtili,), as well as most of the recognized compounds in most plants were aromatic or saturated organic compounds which enabled the plants to be active against the gastrointestinal microbes. The commonly used diluents were; water, methanol and Di methyl sulphate oxides to ascertain the level of activity of the plants. As such, plant materials in one way or the other are very active when dealing with microbes due to their active ingredients or the phytoconstituents. Most of the microbes identified in many reviewed researches were enteric bacterial species, by which divided into both gram negative and gram positive bacterial isolates, they differ in their cell components, which are the main targets of bioactive constituents to deal with any bacteria. However, certain parasites contributed towards the production of ailments for their survival and causing havoc to the hosts and sometimes be mutualistic.